The study on production and strength of arch pan as permanent formwork for floor SLABS - Zaid Fikri , Zainal Rashid (2014)
The increasing cost of materials in the construction industry, new types of construction methods need to be introduced. The application of permanent formwork can reduce the wastage produced hence reduce the construction costs. This is because the formwork will remain permanent on the structure and there is no need to dismantle the formwork. This project aims to introduce arch pan as permanent formwork for the slabs by experimental investigation. The scope of this research is focused particularly on the method of producing arch pan as permanent formwork for the floor slabs. This research also includes laboratory testing for the samples in order to get the strength characteristics of the structure. The experiment shows that this arch pan can be used as permanent formwork for the floor slabs structures. Keywords: arch pan, concrete, plastic netting, plastic mesh, formwork